Fly ash geopolymer grouting material suitable for soft rock reinforcement

CN118255547BActive Publication Date: 2026-10-09HENAN POLYTECHNIC UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410227019.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-29
Publication Date
2026-10-09
Estimated Expiration
2044-02-29

AI Technical Summary

Technical Problem

[0010]本发明的目的在于提供一种适用于软弱围岩加固的粉煤灰地聚物注浆材料,具有浆液稳定性好、流动性好、适宜注浆现场施工等优点,以解决现有的粉煤灰注浆材料施工不便、使用效果不稳定等问题,适用于注浆加固,改善煤矿巷道变形,加固顶板等领域

Benefits of technology

[0023] (1) In this invention, adhesive powder, sodium sulfate, sodium carbonate and quicklime are wrapped in a polymethyl methacrylate shell. When preparing fly ash grouting material, the core material inside the shell will not come into contact with other components in the grout, so as not to affect the preparation process of fly ash grouting material, reducing the impact of grouting material on grouting equipment and grouting pipeline. The adhesive powder is hydrophobic, which can significantly improve the hydrophobic effect of fly ash grouting stone body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118255547B_ABST
    Figure CN118255547B_ABST
Patent Text Reader

Abstract

The application discloses a fly ash geopolymer grouting material suitable for soft surrounding rock reinforcement and relates to the technical field of grouting materials.The grouting material comprises fly ash 70-100 parts, slag powder 30-60 parts, water 70-100 parts and modified microspheres 10-20 parts in terms of weight percentage.The modified microspheres comprise a shell and a core material covered by the shell, and the core material comprises glue powder, anhydrous sodium sulfate, sodium carbonate and slaked lime.The activator is wrapped in the microspheres and used for activating high-content fly ash geopolymer grouting material, and the activator does not contact the components outside the microspheres when the grouting material is prepared, so that the grouting material does not affect the slurry fluidity and stability of the fly ash geopolymer grouting material.The modified microspheres provided by the application can activate high-content fly ash geopolymer grouting material, have the advantages of controllable setting time and good consolidation effect, and can solve the problems of inconvenient construction and unstable use effect of the existing fly ash grouting material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of grouting materials technology, specifically relating to a fly ash geopolymer grouting material suitable for reinforcing weak surrounding rock. Background Technology

[0002] Coal is a pillar of my country's energy system; therefore, promoting the construction of safe and efficient coal mines is an important measure in the new energy security strategy. The excavation of coal mine roadways causes changes in ground stress, leading to the fracturing and expansion of the surrounding rock strata under stress, thus forming fractured zones. As the fractured zones expand, rock strata slide and cause roadway deformation, increasing the difficulty of coal mining and creating significant safety hazards.

[0003] Currently, using a combination of various forms of roadway support and reinforcement is an important means of controlling roadway deformation. In order to improve the control effect of roadway surrounding rock and reduce roadway maintenance costs, it is necessary to develop high-performance and low-cost grouting reinforcement materials to replace traditional cement grouting materials.

[0004] Fly ash is an industrial byproduct of coal combustion in thermal power plants, exhibiting pozzolanic effect, morphological effect, and micro-aggregate effect. Fly ash particles are small in size and have a spherical microstructure. When mixed with other auxiliary cementitious materials, it can be used to prepare geopolymer grouting materials, which have advantages such as good grout flowability and stability. Compared with traditional cement-based grouting materials, it has advantages such as stable performance, wide availability of raw materials, low cost, and controllable setting time.

[0005] Currently, the performance improvement of fly ash geopolymer grouting materials is mainly achieved by adding cement, water glass, and NaOH, for example:

[0006] Chinese Patent 110256038A discloses a slag-fly ash grouting filler material and its preparation method. The method involves uniformly mixing weighed slag powder, fly ash, water-reducing agent, water, elastic emulsion, and styrene-acrylic emulsion to prepare liquid A, and uniformly mixing water glass solution and KOH to prepare liquid B. Liquids A and B are then mixed, and an antifoaming agent is added to obtain a high-performance grouting filler material. However, the overall process is quite cumbersome and not suitable for on-site grouting applications.

[0007] Chinese patent CN111825393A discloses a method for proportioning high-volume fly ash grouting raw materials. The method involves mixing cement, fly ash, and water to obtain the grouting material, and then activating the high-volume fly ash grouting raw material with Ca(OH)2 and NaCl to obtain a fly ash grouting material that meets the strength and setting time requirements for grouting reinforcement of the roof slab. However, in large-scale grouting processes, the cost of fly ash cement grouting raw materials remains significantly higher than that of geopolymer grouting raw materials.

[0008] Chinese patent CN108558350A discloses a fly ash grouting material and its preparation method. This grouting material consists of component A (fly ash, ammonium dihydrogen phosphate, potassium dihydrogen phosphate, pH adjuster, defoamer stabilizer, and chopped fibers) and component B (magnesium oxide, polymer emulsion, anti-water dispersing agent, retarder, and ultrafine filler). Mixing these two components produces a fly ash grouting material with good early strength and fluidity. However, the defoamer stabilizer is insufficient to remove the large number of air bubbles introduced by the polymer during stirring, affecting the strength of the grouting material after injection.

[0009] Therefore, there is a need to provide a fly ash grouting material with good slurry stability, good fluidity, and suitability for on-site grouting construction. Summary of the Invention

[0010] The purpose of this invention is to provide a fly ash geopolymer grouting material suitable for reinforcing weak surrounding rock. It has the advantages of good grout stability, good fluidity, and suitability for on-site grouting construction, so as to solve the problems of inconvenient construction and unstable performance of existing fly ash grouting materials. It is suitable for grouting reinforcement, improving coal mine roadway deformation, and reinforcing the roof.

[0011] To achieve the above objectives, the present invention provides the following technical solution:

[0012] A fly ash geopolymer grouting material suitable for reinforcing weak surrounding rock comprises, by weight, 70-100 parts fly ash, 30-60 parts slag powder, 70-100 parts water, and 10-20 parts modified microspheres. The modified microspheres include a shell and a core material covered by the shell. The core material includes adhesive powder, sodium sulfate, sodium carbonate, and quicklime.

[0013] Preferably, the modified microspheres are high-pressure release microspheres.

[0014] Preferably, the shell ruptures under an external pressure ≥4MPa, releasing the core material.

[0015] Preferably, the shell material is polymethyl methacrylate.

[0016] Preferably, the slag powder is S95 grade slag powder.

[0017] Preferably, the fly ash is grade II or higher fly ash.

[0018] Preferably, by weight, the core material comprises 15-30 parts of adhesive powder, 5-10 parts of sodium sulfate, 5-10 parts of sodium carbonate, and 10-15 parts of quicklime.

[0019] Preferably, by weight, the raw materials of the shell include 20-30 parts of methyl methacrylate, 10-15 parts of surfactant, 5-10 parts of polymerizer, 10-15 parts of initiator, and 45-70 parts of solvent.

[0020] Preferably, the particle size of the slag powder does not exceed 20 μm.

[0021] Preferably, the particle size of the fly ash does not exceed 10 μm.

[0022] Beneficial effects:

[0023] (1) In this invention, adhesive powder, sodium sulfate, sodium carbonate and quicklime are wrapped in a polymethyl methacrylate shell. When preparing fly ash grouting material, the core material inside the shell will not come into contact with other components in the grout, so as not to affect the preparation process of fly ash grouting material, reducing the impact of grouting material on grouting equipment and grouting pipeline. The adhesive powder is hydrophobic, which can significantly improve the hydrophobic effect of fly ash grouting stone body.

[0024] (2) The present invention first prepares modified microspheres coated with activators, and then incorporates them into fly ash grouting materials for use as single-liquid grouting materials. The preparation process is simple, the stability is good, and it is convenient for on-site grouting construction.

[0025] (3) The grouting material provided by the present invention can adjust the setting and hardening time of the grout after injection by adjusting the amount of modified microspheres and the ratio of core material. The initial setting time is 30min-8h and the final setting time is 2-12h. It is suitable for grouting reinforcement and filling of water-blocking areas and roof slabs. While improving the bonding strength of fly ash grouting material, it also solves the problems of low strength and uncontrollable setting time of existing geopolymer grouting materials. Attached Figure Description

[0026] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. Wherein:

[0027] Figure 1 This is a schematic diagram of the structure of the modified microspheres prepared in Example 1 of the present invention.

[0028] Figure 2 This is a schematic diagram illustrating the mechanism of action of a fly ash geopolymer grouting material suitable for reinforcing weak surrounding rock, prepared in Example 1 of the present invention. Detailed Implementation

[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention are within the scope of protection of the present invention.

[0030] The present invention will now be described in detail with reference to embodiments. It should be noted that, unless otherwise specified, the embodiments and features described in the embodiments of the present invention can be combined with each other.

[0031] This invention addresses the problems of cumbersome preparation processes, insufficient strength, and high costs associated with current grouting materials. It provides a fly ash geopolymer grouting material suitable for reinforcing weak surrounding rock. By weight, it comprises 70-100 parts fly ash (e.g., 71, 75, 80, 85, 90, 95, 99 parts), 30-60 parts slag powder (e.g., 31, 35, 40, 45, 50, 55, 59 parts), 70-100 parts water (e.g., 71, 75, 80, 85, 90, 95, 99 parts), and 10-20 parts modified microspheres (e.g., 11, 12, 13, 14, 15, 16, 17, 18, 19 parts). The modified microspheres include a shell and a core material encapsulated by the shell. The core material includes adhesive powder, sodium sulfate, sodium carbonate, and slaked lime.

[0032] The material properties and technical principles selected in this invention are as follows:

[0033] First, the fly ash and slag powder used in this invention have small particle size and large specific surface area, which can improve the reactivity of fly ash. At the same time, the finer raw materials can make the slurry properties of fly ash grouting materials more stable and form a denser stone body. The CaO in the slag powder is conducive to the hydration of fly ash and promotes the formation of hydration products CASH and NASH gel.

[0034] Secondly, the modified microspheres used in this invention, by encapsulating a core containing an activator in a shell, can reduce the impact of the activator on the properties of the grout during the grouting process.

[0035] Finally, sodium sulfate, sodium carbonate, and quicklime are used as activators to enhance the pozzolanic effect of fly ash. The glassy network structure of fly ash dissolves in an alkaline environment, releasing soluble particles that exchange ions with the surrounding environment. This promotes the deagglomeration of the glassy network structure, forming a large number of monomers. Under the attraction of hydroxyl groups, these monomers form intermediate complexes. As Ca... 2+ The addition of network modifiers further forms stable hydration products, and the addition of adhesive powder can improve the adhesion of fly ash grouting materials.

[0036] In a preferred embodiment of the present invention, the modified microspheres are high-pressure release microspheres.

[0037] In a preferred embodiment of the present invention, the shell ruptures under an external pressure ≥4MPa and releases the core material.

[0038] In a preferred embodiment of the present invention, the shell material is polymethyl methacrylate.

[0039] In a preferred embodiment of the present invention, the slag powder is S95 grade slag powder.

[0040] In a preferred embodiment of the present invention, the fly ash used is grade II or higher fly ash.

[0041] In a preferred embodiment of the present invention, the core material comprises, by weight, 15-30 parts of adhesive powder (e.g., 16, 18, 20, 22, 24, 26, 28, or 29 parts), 5-10 parts of sodium sulfate (e.g., 6, 7, 8, or 9 parts), 5-10 parts of sodium carbonate (e.g., 6, 7, 8, or 9 parts), and 10-15 parts of quicklime (e.g., 11, 12, 13, or 14 parts).

[0042] In a preferred embodiment of the present invention, the raw materials for the shell, by weight, include 20-30 parts of methyl methacrylate (e.g., 21, 22, 23, 24, 25, 26, 27, 28, or 29 parts), 10-15 parts of surfactant (e.g., 11, 12, 13, or 14 parts), 5-10 parts of polymerizing agent (e.g., 6, 7, 8, or 9 parts), 10-15 parts of initiator (e.g., 11, 12, 13, or 14 parts), and 45-70 parts of solvent (e.g., 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, or 69 parts).

[0043] In a preferred embodiment of the present invention, the particle size of the slag powder does not exceed 20 μm.

[0044] In a preferred embodiment of the present invention, the particle size of fly ash does not exceed 10 μm.

[0045] This invention also proposes a method for preparing the above-mentioned modified microsphere-activated high-content fly ash geopolymer grouting material, which includes the following steps:

[0046] S1. Methyl methacrylate, surfactant, polymerizer and initiator are ultrasonically emulsified using an ultrasonic instrument to obtain the shell material;

[0047] S2. Mix the glue powder, sodium sulfate, sodium carbonate and quicklime evenly to obtain the core material;

[0048] S3. Mix the core material and shell material evenly, and then evaporate them in a rotary evaporator to obtain powder;

[0049] S4. Dry the powder from step S3 and grind it to below 200 to obtain modified microspheres;

[0050] S5. Weigh out 70-100 parts of fly ash, 30-60 parts of slag powder, 70-100 parts of water, and 10-20 parts of modified microspheres according to the proportions, mix them evenly and set aside.

[0051] The following detailed description of a fly ash geopolymer grouting material suitable for reinforcing weak surrounding rock is provided through specific embodiments.

[0052] The sources of raw materials used in the following examples and comparative examples are as follows:

[0053] Methyl methacrylate, 95% purity, purchased from Shanghai E. En Chemical Technology Co., Ltd.

[0054] The initiator was benzoyl peroxide, 98% pure, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0055] The surfactant was arylalkylcarboxybetaine (BCB), with a purity of 99%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0056] The polymerizing agent was triethylaluminum, with a purity of 98%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0057] The alcohol solvent was anhydrous ethanol with a purity of 99.5%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0058] The sodium sulfate is industrial grade sodium sulfate with a purity greater than 98% (by weight), purchased from Henan Qiangnai New Materials Co., Ltd.

[0059] Sodium carbonate is industrial soda ash with a purity greater than 98% (by weight), purchased from Henan Qiangnai New Materials Co., Ltd.

[0060] The quicklime was industrial calcium hydroxide with a purity greater than 98% (by weight), purchased from Henan Qiangnai New Materials Co., Ltd.

[0061] The adhesive powder is a redispersible adhesive powder, purchased from Anhui Wanwei Group Co., Ltd.

[0062] The mineral powder is grade S95 and was purchased from Longze Water Purification Materials Co., Ltd.

[0063] The fly ash is Class II fly ash, purchased from Shanxi Zhangze Power Co., Ltd.

[0064] In the following embodiments, the ultrasonic instrument is model JY92-IIN.

[0065] Example 1

[0066] Preparation of a fly ash geopolymer grouting material suitable for reinforcing weak surrounding rock:

[0067] The raw materials for the modified microspheres, by weight, are: 30 parts methyl methacrylate, 10 parts initiator, 10 parts surfactant, 5 parts polymerizing agent, 55 parts alcohol solvent, 20 parts adhesive powder, 10 parts sodium sulfate, 10 parts sodium carbonate, and 15 parts quicklime. In this embodiment, the initiator is benzoyl peroxide, the surfactant is arylalkylcarboxybetaine (BCB), the polymerizing agent is triethylaluminum, the adhesive powder is redispersible adhesive powder, the sodium sulfate is industrial sodium sulfate, the sodium carbonate is industrial sodium carbonate, and the quicklime is industrial calcium hydroxide.

[0068] By weight, the fly ash geopolymer grouting material consists of: 70 parts fly ash, 40 parts slag powder, 70 parts water, and 20 parts modified microspheres.

[0069] A method for preparing a fly ash geopolymer grouting material suitable for reinforcing weak surrounding rock includes the following steps:

[0070] S1. Methyl methacrylate, surfactant, polymerizer and initiator are ultrasonically emulsified using an ultrasonic instrument. The ultrasonic temperature is room temperature, the ultrasonic duration is 40 minutes and the power is 520W to obtain the shell material.

[0071] S2. Mix the glue powder, sodium sulfate, sodium carbonate and quicklime evenly to obtain the core material;

[0072] S3. Mix the core material and shell material evenly so that the core material is coated with the shell material, and then place it in a rotary evaporator for rotary evaporation to obtain powder;

[0073] S4. Dry the powder prepared in step S3 and grind it to below 200 to obtain modified microspheres;

[0074] S5. Weigh out 70 parts fly ash, 30 parts slag powder, 70 parts water, and 20 parts modified microspheres according to the proportion, mix them evenly and set aside. This is the grouting material to be prepared.

[0075] Example 2

[0076] Preparation of a fly ash geopolymer grouting material suitable for reinforcing weak surrounding rock:

[0077] The raw materials for the modified microspheres, by weight, are: 30 parts methyl methacrylate, 10 parts initiator, 10 parts surfactant, 5 parts polymerizing agent, 55 parts alcohol solvent, 7 parts sodium sulfate, 7 parts sodium carbonate, and 10 parts quicklime. In this embodiment, the initiator is benzoyl peroxide, the surfactant is arylalkyl carboxybetaine (BCB), the polymerizing agent is triethylaluminum, the sodium sulfate is industrial sodium sulfate, the sodium carbonate is industrial sodium carbonate, and the quicklime is industrial calcium hydroxide.

[0078] The preparation method is the same as in Example 1. By weight, the fly ash geopolymer grouting material is: 80 parts fly ash, 30 parts slag powder, 100 parts water, and 10 parts modified microspheres.

[0079] The grouting material provided in this embodiment is suitable for grouting reinforcement of the roof slab.

[0080] Example 3

[0081] Preparation of a fly ash geopolymer grouting material suitable for reinforcing weak surrounding rock:

[0082] The raw materials for the modified microspheres, by weight, are: 30 parts methyl methacrylate, 10 parts initiator, 10 parts surfactant, 5 parts polymerizing agent, 55 parts alcohol solvent, 30 parts adhesive powder, 10 parts sodium sulfate, 10 parts sodium carbonate, and 10 parts quicklime.

[0083] The preparation method is the same as in Example 1. By weight, the fly ash geopolymer grouting material is: 70 parts fly ash, 50 parts slag powder, 70 parts water, and 15 parts modified microspheres. It is injected into the coal bonding mold by a high-pressure grouting pump at a grouting pressure of 4.0 MPa. The bonding strength is measured after 1 day, and the setting and hardening time of the grout is also tested, as shown in Table 1.

[0084] Bond strength test:

[0085] The grouting materials prepared in Examples 1 and 3 were injected into the coal bonding mold using a high-pressure grouting pump at a grouting pressure of 4.0 MPa. The bonding strength was measured after 1 day, and the setting and hardening time of the grout was also tested, as shown in Table 1.

[0086] Comparative Example 1

[0087] The modified microspheres prepared in Example 3 were used to activate the high-volume fly ash geopolymer grouting material. The grouting pressure was changed to 3.0 MPa, and the material was injected into the coal bonding mold using a grouting pump. The bonding strength was measured after 1 day, and the setting and hardening time of the grout was also tested, as shown in Table 1.

[0088] Table 1. Setting and hardening time and bond strength of different grouting materials

[0089]

[0090]

[0091] As shown in Table 1 above, a comparison of Examples 1 and 3 with Comparative Example 1 shows that grouting pressures below 4.0 MPa significantly limit the release of modified microsphere core material, increasing the setting time from 0.4–0.5 h to 1.2 h, while the bonding strength decreases.

[0092] Slurry performance testing:

[0093] The modified microsphere-activated high-volume fly ash geopolymer grouting material prepared in Example 2 was subjected to grout performance tests, and its performance was compared with that of traditional cement-based grouting reinforcement materials (usually composed of ordinary Portland cement, lime, gypsum, and expanding agents and early-strength agents). The fluidity was measured using a Marvimeter funnel (MLN-3); the grout stone formation rate was measured using a 100ml plastic graduated cylinder; and the setting and hardening time of the grout and the strength of the formed stone are shown in Table 2.

[0094] Table 2. Relevant properties of the grouting material prepared in Example 2

[0095]

[0096] When reinforcing the roof slab directly over a collapse zone, the roof slab strength must be greater than 1 MPa, and the grout properties must be stable. As shown in Table 2 above, compared to cement-based grouting reinforcement materials, the grouting material provided in Example 2 has the same stability and better fluidity while having lower raw material costs.

[0097] In summary, this invention utilizes modified microspheres to activate high-volume fly ash geopolymer grouting materials. During high-pressure grouting, the microspheres within the grouting material rupture, releasing the activator and accelerating the setting time of the grouted material, thus significantly improving its bonding strength. Because the activator is encapsulated within the shell, it does not come into contact with other components during grouting and mixing, preventing the fly ash grouting material from affecting the grout's properties during mixing. This avoids the fly ash grouting material from solidifying during grouting or even mixing, which could negatively impact grouting equipment and on-site construction.

[0098] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A fly ash geopolymer grouting material suitable for reinforcing weak surrounding rock, characterized in that, The product comprises, by weight, 70-100 parts fly ash, 30-60 parts slag powder, 70-100 parts water, and 10-20 parts modified microspheres. The modified microspheres include a shell and a core material covered by the shell. The core material includes adhesive powder, sodium sulfate, sodium carbonate, and quicklime. The modified microspheres are high-pressure release type microspheres; The shell ruptures under an external pressure ≥4MPa, releasing the core material; The shell is made of polymethyl methacrylate and the solvent is alcohol.

2. The fly ash geopolymer grouting material for reinforcing weak surrounding rock as described in claim 1, characterized in that, The slag powder used is S95 grade slag powder.

3. The fly ash geopolymer grouting material suitable for reinforcing weak surrounding rock as described in claim 1, characterized in that, The fly ash used is grade II or higher.

4. The fly ash geopolymer grouting material suitable for reinforcing weak surrounding rock as described in claim 1, characterized in that, By weight, the core material comprises 15-30 parts of adhesive powder, 5-10 parts of sodium sulfate, 5-10 parts of sodium carbonate, and 10-15 parts of quicklime.

5. The fly ash geopolymer grouting material suitable for reinforcing weak surrounding rock as described in claim 1, characterized in that, By weight, the raw materials of the shell include 20-30 parts of methyl methacrylate, 10-15 parts of surfactant, 5-10 parts of polymerizer, 10-15 parts of initiator, and 45-70 parts of solvent.

6. The fly ash geopolymer grouting material suitable for reinforcing weak surrounding rock as described in claim 2, characterized in that, The particle size of the slag powder does not exceed 20 μm.

7. The fly ash geopolymer grouting material suitable for reinforcing weak surrounding rock as described in claim 3, characterized in that, The particle size of the fly ash shall not exceed 10 μm.

Citation Information

Patent Citations

  • Fly ash grouting material and preparation method thereof

    CN108558350A

  • Proportioning method of high-volume fly ash grouting raw material

    CN111825393A

  • Slag powder and coal ash grouting-filling material and preparation method thereof

    CN110256038A

  • In-situ polymerization modified inorganic grouting material and preparation method thereof

    CN110272253A